Sydpolen, fra drøm til virkelighet - Arnesen, Liv (Polarboken, 1996)
Keywords: Antarktis; ekspedisjoner

A force-balance study of ice flow and basal conditions of Jutulstraumen, Antarctica - Høydal, Øyvind Armand (Journal of Glaciology, 1996)
Stresses and velocities at depth are calculated across Jutulstraumen, an ice stream in Dronning Maud Land, draining about 1% of the Antarctic ice sheet. The force-balance study is based on data from kinematic GPS measurements on three strain nets, each consisting of 3 × 3 stakes. The maximum measured velocity is 443 m a−1 and the velocity variation over short distances is large compared with studied ice streams in West Antarctica. The surface topography together with the measured velocities across the profile indicate that the bottom topography has a great influence on the flow direction, even where the ice thickness is more than 2000 m. The basal shear stresses are calculated as 180, 227 and 146 kPa in the three Strain nets, while the corresponding driving stresses are 180, 122 and 111 kPa (±5%). The heat produced by sliding and internal deformation is sufficient to keep the base at the pressure-melting point. The annual basal melting is estimated to be about 60 mm. Investigations on the effect of temperature softening show that the flow parameter’s influence on the effective strain rate is more important than the flow parameter’s direct softening in the flow low alone. The mass flow calculated by the force-balance method is between 87 and 96% of pure plug flow and total discharge is calculated to be 13.3 ± 10 km3a-1.
Keywords: Dronning Maud Land; glasiologi; innlandsis; isstrøm

Den nordiske Antarktisekspedisjonen 1995/1996: Rapport om grunn kjerneboring på kontinentalsokkelen i Weddelhavet, Antarktis - Kristoffersen, Yngve (Inst. for den faste jords fysikk, UiB, 1996)
Keywords: Sørishavet; ekspedisjoner; geologi

Et eksperiment i egenmestring - Pedersen, Cato Zahl (Polarboken, 1996)
Keywords: Antarktis; ekspedisjoner

Governing the Antarctic : the effectiveness and legitimacy of the Antarctic Treaty System - Støkke, Olav Schram (ed.); Vidas, Davor (ed.) (Cambridge University Press, 1996)
Keywords: Antarktis; Antarktistraktaten 1959; internasjonal politikk; polarområdene; politikk

Mites collected in Heimefrontfjella and Vestfjella (Dronning Maud Land, Antarctica) - Thor, Göran (Fauna norvegica. Serie B, 1996)
Keywords: Dronning Maud Land; dyr; midder; zoologi

Melting, runoff and the formation of frozen lakes in a mixed snow and blue-ice field in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar; Elvehøy, Hallgeir; Bøggild, Carl Egede; Sand, Knut; Liston, Glen (Journal of Glaciology, 1996)
Large-scale melting phenomena such as meltwater drainage channels and meltwater accumulation basins of frozen lakes were surveyed on the land ice mass in Jutulgryta, Dronning Maud Land, Antarctica, during the Norwegian Antarctic Research Expedition in 1989–90 (NARE 1989–90). The largest frozen lake that was observed was close to 1 km in width. These melting features were also detected in a Landsat Thematic Mapper image recorded on 12 February 1990. Then, during NARE 1993–94, a 5year glaciological programme was started in this area. In spite of negative air temperatures and the presence of a frozen ice surface, sub-surface melting and runoff were found within the uppermost metre in blue-ice fields. The sub-surface melting is a consequence of solar radiative penetration and absorption within the ice, i.e. the “solid-state-greenhouse effect”. Temperatures in blue ice were about 6°C higher than for snow. Internal melt and meltwater transport were observed throughout the 1 month of measurements. The conditions for active melting in Jutulgryta are probably marginal. A slight increase of air temperatures can result in more “classical” surface melting, whereas a cooling may disable sub-surface melting. Studies of how the extent and characteristics of the melting features change with time can be particularly valuable as indicators of climate change. This ongoing programme clearly identifies the importance of analyzing how these melting features originate, of mapping their present areal distribution, of determining how sensitive they are to climate change and of Studying changes in the past and possible changes in the future.
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1993/94; blåis; fjernanalyse; glasiologi; klimaendringer; satellitteknologi

Plans for the EPICA DML pre site survey 96/97 - Winther, Jan-Gunnar; van den Broeke, Michiel (Filchner-Ronne Ice Shelf Programme. Report, 1996)
Keywords: Dronning Maud Land; glasiologi